ARIMA METHOD MODELING IN PREDICTING THE DAILY STOCK PRICE OF PT GARUDA INDONESIA DURING THE COVID-19 PANDEMIC - Niel Ananto; Cherry Lumingkewas (Faculty of Economics and Business, Universitas Klabat, 2022)
The main purpose of this research is to create a predictive model of the ARIMA method on the daily stock price of PT. Garuda Indonesia, Tbk during the Covid-19 pandemic. This study uses daily secondary data from April 22, 2019, to April 20, 2020. The results of research using the ARIMA model shows that data from April 22, 2019, to April 20, 2020, can be used to predict stock closing prices from April 21, 2020, to July 13, 2020. The ARIMA model obtained the results of daily stock price predictions of PT. Garuda Indonesia, Tbk on the Indonesia Stock Exchange from 21 April 2020 to 13 July 2020 tend to experience a decline. This is presumably because investors tend to hold back their capital due to the government's prohibition on going home, which resulted in the cessation of operations in the aviation sector. Keywords: Covid-19, Garuda Indonesia, stock price, ARIMA method.